2013
DOI: 10.1111/j.1447-0756.2012.02067.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and adverse outcomes of inadequate or excessive gestational weight gain in an Asian population

Abstract: Maternal predictors and perinatal outcomes of GWG among Asian women are similar to those identified previously among Caucasian, African-American and Hispanic women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 32 publications
4
35
0
1
Order By: Relevance
“…16,25 However, like other studies, 8,20 we failed to find the association between prepregnancy BMI and preterm delivery. Consistent with the previous study that used total GWG as exposure variable, 10 we found women who gained less had a higher risk of preterm delivery. Furthermore, previous studies using the average rate of GWG as exposure variable provided stronger evidence about this association.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…16,25 However, like other studies, 8,20 we failed to find the association between prepregnancy BMI and preterm delivery. Consistent with the previous study that used total GWG as exposure variable, 10 we found women who gained less had a higher risk of preterm delivery. Furthermore, previous studies using the average rate of GWG as exposure variable provided stronger evidence about this association.…”
Section: Discussionsupporting
confidence: 92%
“…2,4 Several previous studies have shown that high prepregnancy body mass index (BMI) or excessive GWG may be associated with increased risks of maternal and neonatal outcomes including gestational diabetes mellitus (GDM), 5,6 hypertensive disorders in pregnancy (HDP), caesarean delivery, large for gestational age infant (LGA), 7,8 and macrosomia. 9,10 Conversely, underweight or inadequate GWG may contribute to the increased risks of low birth weight (LBW) and small for gestational age infant (SGA). 6,10 However, some of the findings are not consistent, especially for the effect of GWG on GDM (since women who are diagnosed as GDM would take lifestyle interventions to control weight gain, it is more reasonable to use weight gain before diagnosis instead of total GWG as exposure variable).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences may also relate to ethnic variation. In Singapore, difference in GWG between ethnicities was postulated to be due to difference in diet quality and psychosocial factors [55]. However we postulate that the degree of observed difference primarily related to application of BMI categories.…”
Section: Discussionmentioning
confidence: 86%
“…Asian studies have already suggested the need for specific guidelines [56]. In 2000, Chinese-specific guidelines for GWG [57] were developed, but have not been commonly adopted, with most Asian studies using mainly Caucasian-derived IOM GWG guidelines [55]. A call has been made for multi-centre collaboration to create optimal GWG guidelines for Asian women using modified BMI categories [58].…”
Section: Discussionmentioning
confidence: 99%